Elucidating the formation mechanism of gardenia blue pigment from amino acid and genipin - Xiaoyu Zhang; Ruihu Zhang; Rui Li; Jiaxing Zhang; Yuefei Wang; Xin Chai; Yuefei Wang (Arabian Journal of Chemistry)
Gardenia blue (GB), a natural active blue pigment, can be synthesized from iridoid glycosides and primary amino-containing compounds in vivo and in vitro. However, limited studies have reported about GB synthetic intermediates, leading to unawareness of the formation mechanism of GB. Here, we reported that GB could be detected in rats′ feces, whose formation was simulated by in vitro reaction of amino acid-rich feces extract from rats and genipin (GP) metabolized from geniposide (GE) through β-glucosidase. Firstly, we proved that 14 amino acids (AAs) detected in rats′ feces containing primary amino groups can react with GP to produce GB. Then, taking histidine (His) as example, we characterized the key intermediates during the reaction process, including basic units genihistidine A (GH-A) and dimers. As an active basic unit, GH-A underwent covalent polymerization to form dimer, which then self-assembled into supramolecular spherical nanoparticles through multiple noncovalent interactions, including hydrogen bonds, π-π interactions, and van der Waals interactions. Our study revealed the formation mechanism of GB and provided insights into the bioavailable form of GE from traditional Chinese medicine in vivo.